Candidate methylation sites associated with endocrine therapy resistance in ER+/HER2- breast cancer - Soleimani Dodaran, Maryam; Borgoni, Simone; Sofyali, Emre; Verschure, Pernette J.; Wiemann, Stefan; Moerland, Perry D.; van Kampen, Antoine H. C. (BMC cancer, 2020)
Estrogen receptor (ER) positive breast cancer is often effectively treated with drugs that inhibit ER signaling, i.e., tamoxifen (TAM) and aromatase inhibitors (AIs). However, 30% of ER+ breast cancer patients develop resistance to therapy leading to tumour recurrence. Changes in the methylation profile have been implicated as one of the mechanisms through which therapy resistance develops. Therefore, we aimed to identify methylation loci associated with endocrine therapy resistance.
Gesehen am 01.09.2020